SMOKING AMONG DOCTORS OF MILITARY HOSPITAL RAWALPINDI; FREQUENCY, HABITS AND ATTITUDES: Smoking Among Doctors - Zeeshan, Mansoor; Ahmed, Waqar (Pakistan Armed Forces Medical Journal, 2009)
Objectives: To know the frequency of smoking habit among doctors of Military Hospital Rawalpindi and to know their attitudes towards it. Study Design: Questionnaire based descriptive study. Place and Duration of Study: The study was conducted at Department of Medicine, Military Hospital, Rawalpindi from December 2004 to May 2005. Subjects and Methods: 106 doctors from Military Hospital, Rawalpindi were included either by direct interviews or by filling of questionnaires by the participants. Results: Smokers, all male, were 18 (17% of responders). Mean age of starting smoking was 19.4 years. Average number of cigarettes smoked per day was 12.6. Among smokers 11 (61.1%) were not willing to quit smoking. A majority of non-smoker doctors considered themselves as role models and agreed that smoking at public places should be prohibited. Conclusion: Smoking among doctors in this study is not high however there is less willingness to combat smoking habits of patients in doctors who smoke. A continuing education program should be instituted to motivate doctors about their role in society.